Eksplorasi Spiritual Anak di Era Digital: Prespektif Psikologi Agama Islam - Irmayanti (putrapublisher.org, 2023)
In today's digital era, children are increasingly exposed to various technologies that influence their spiritual development. This study aims to dig deeper into how digital technology impacts children's spiritual exploration, as well as providing guidance for parents and teachers in facing this challenge. Using an Islamic religious psychology approach, this research will analyze the impact of digital technology on children's understanding of spirituality, as well as strategies that can be used to strengthen spiritual values in everyday life. Through this study, it is hoped that it can provide better understanding for parents and teachers in accompanying children in developing their spiritual dimensions in the midst of the ever-growing digital era.